Conductive carbon black, positive pole piece, electrochemical device and electronic device

By using conductive carbon black in the positive electrode sheet of lithium battery to build an efficient conductive network, the problem of low energy conversion efficiency of lithium battery is solved, more efficient electron transmission and lower cell expansion rate are achieved, and the stability and safety of the battery are improved.

CN119890315APending Publication Date: 2025-04-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510371843.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The energy conversion efficiency of lithium batteries is low during charging and discharging, resulting in a sudden drop in voltage and a decrease in power output performance, affecting the operation stability of the equipment.

Method used

Conductive carbon black is used to build an efficient conductive network in the positive electrode sheet, reducing the resistance of the positive electrode sheet, thereby improving the energy conversion efficiency of the electrochemical device.

Benefits of technology

By reducing the DC internal resistance of the electrochemical device, it improves the smoothness of electron transmission, reduces energy loss during charging and discharging, improves the energy conversion efficiency of the electrochemical device, and reduces the cell thickness expansion rate in high-temperature environments, improving stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses conductive carbon black, a positive pole piece, an electrochemical device and an electronic device. The conductive carbon black comprises a plurality of carbon black units and pores located between the adjacent carbon black units; based on the total mass of the conductive carbon black, the volatile component in the conductive carbon black is M%, the specific surface area of the conductive carbon black is Nm < 2 > / g, and the conductive carbon black meets the condition that M / N is more than or equal to 0.003 and less than or equal to 0.02. According to the conductive carbon black disclosed by the embodiment of the invention, an efficient conductive network can be constructed in the positive pole piece, and the resistance of the positive pole piece is reduced, so that the energy conversion efficiency of the electrochemical device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical devices, and in particular to a conductive carbon black, a positive electrode sheet, an electrochemical device and an electronic device. Background Art

[0002] With the booming development of electronic equipment and new energy vehicle industries, lithium battery performance faces extremely stringent requirements. However, in actual working conditions, lithium batteries have exposed many disadvantages in different environments and working conditions. For example, energy waste during charging and discharging, and voltage drops caused by internal resistance in scenarios such as electric vehicle startup that have high requirements for instantaneous high current output, seriously affect power output performance and reduce equipment operation stability.

[0003] Therefore, how to effectively solve the problem of low energy conversion efficiency of lithium batteries has become the key to improving the comprehensive performance of lithium batteries. Summary of the invention

[0004] The present application provides a conductive carbon black, a positive electrode sheet, an electrochemical device and an electronic device. The conductive carbon black can construct an efficient conductive network in the positive electrode sheet, reduce the resistance of the positive electrode sheet, and thus improve the energy conversion efficiency of the electrochemical device.

[0005] In a first aspect, the present application provides a conductive carbon black, which comprises a plurality of carbon black units and pores between adjacent carbon black units; based on the total mass of the conductive carbon black, the volatile matter in the conductive carbon black is M%, and the specific surface area of ​​the conductive carbon black is Nm 2 / g, conductive carbon black satisfies: 0.003≤M / N≤0.02.

[0006] According to the present application, when the conductive carbon black of the present application is used and the conductive carbon black satisfies 0.003≤M / N≤0.02, the conductive carbon black can construct an efficient conductive network in the positive electrode sheet. On the one hand, it can reduce the DC internal resistance of the electrochemical device, make the electron transmission smoother, reduce the energy loss during the charging and discharging process, and improve the energy conversion efficiency of the electrochemical device. On the other hand, it can enhance the interaction between the conductive carbon black and the electrode material, improve the structural stability of the electrode material, reduce the structural changes caused by high temperature, maintain a good contact state between the electrode material and the electrolyte, and thus inhibit the expansion of the battery cell thickness. In addition, the thickness expansion rate of the battery cell is reduced, and the stability and safety of the electrochemical device in a high temperature environment are improved.

[0007] In some specific embodiments, the conductive carbon black satisfies: 0.005≤M / N≤0.01.

[0008] In the above embodiment, when the conductive carbon black satisfies: 0.005≤M / N≤0.01, it can further reduce the energy loss during the charging and discharging process, improve the energy conversion efficiency of the electrochemical device, and at the same time, further improve the structural stability of the electrode material, reduce the thickness expansion rate of the battery cell, and improve the stability and safety of the electrochemical device in a high temperature environment.

[0009] In some specific embodiments, based on the total mass of the conductive carbon black, the mass percentage of volatile matter in the conductive carbon black is 0.1% to 0.7%, and / or the specific surface area of ​​the conductive carbon black is 30 m 2 / g~80m 2 / g.

[0010] In the above specific implementation, when the volatile matter in the conductive carbon black is 0.1% to 0.7%, the binder can better combine with the conductive agent, and the volatile matter can make the conductive agent more evenly distributed, and together with the binder, it plays a certain "coating effect" on the electrode material, reducing the direct contact between the positive electrode material and the electrolyte, reducing side reactions, improving the thickness expansion rate of the battery cell at high temperature, and improving the stability and safety of the electrochemical device in a high temperature environment. If the specific surface area of ​​the conductive carbon black is too small, the effective conductive area is reduced, thereby increasing the DC internal resistance of the electrochemical device, and causing the conductive carbon black dispersion effect to deteriorate, reducing the coating of the positive electrode active material, thereby increasing the thickness expansion rate of the battery cell.

[0011] In some specific embodiments, based on the total mass of the conductive carbon black, the mass percentage of volatile matter in the conductive carbon black is 0.3% to 0.6%, and / or the specific surface area of ​​the conductive carbon black is 50 m 2 / g~70m 2 / g.

[0012] In the above specific implementation manner, the volatile matter in the conductive carbon black is 0.3% to 0.6%, and / or the specific surface area of ​​the conductive carbon black is 50m 2 / g~70m 2 / g, on the one hand, it further promotes the transmission of electrons in the positive electrode material, and on the other hand, it further reduces the DC internal resistance of the electrochemical device, allowing electrons to flow from the external circuit into the positive electrode active material to participate in the electrochemical reaction more efficiently, or flow out from the positive electrode active material to the external circuit, reducing energy loss, thereby significantly improving the energy conversion efficiency of the electrochemical device. At the same time, it stabilizes the interface between the electrode material and the electrolyte, further inhibits the excessive expansion of the battery cell thickness, effectively reduces the battery cell thickness expansion rate, and further improves the stability and safety of the electrochemical device in a high temperature environment. Further preferably, the specific surface area of ​​the conductive carbon black is 50m 2 / g~60m 2 / g, which can better improve the energy conversion efficiency of electrochemical devices. At the same time, it can better stabilize the interface between electrode materials and electrolytes, inhibit excessive expansion of the battery thickness, effectively reduce the expansion rate of the battery thickness, and better improve the stability and safety of electrochemical devices in high temperature environments.

[0013] In some specific embodiments, based on the total mass of the conductive carbon black, the conductive carbon black includes A% of oxygen elements, the conductive carbon black includes B% of hydrogen elements, and the conductive carbon black satisfies: 0.5≤A / B≤2.

[0014] In the above specific embodiment, when the conductive carbon black satisfies: 0.5≤A / B≤2, the chemical properties of the conductive carbon black surface can be optimized. The oxygen-containing functional groups and hydrogen-containing structures on the surface of the conductive carbon black are adjusted. The two work together to optimize the conductive network constructed by the conductive carbon black, improve the efficiency of electron transmission, reduce the DC internal resistance of the electrochemical device, and reduce the energy loss during the charge and discharge process, thereby improving the energy conversion efficiency of the electrochemical device. At the same time, the stabilizing effect of the conductive carbon black on the electrode material structure can be enhanced. The synergistic effect of the two can reduce the structural changes of the electrode material caused by high temperature, maintain a good contact state between the electrode material and the electrolyte, and the binder can better combine with the conductive agent, and the volatiles can make the conductive agent more evenly distributed. Together with the binder, it plays a certain "coating effect" on the electrode material, reducing the direct contact between the positive electrode material and the electrolyte, reducing side reactions, and improving the thickness expansion rate of the battery cell. The binder can better combine with the conductive agent, and the volatiles can make the conductive agent more evenly distributed. Together with the binder, it plays a certain "coating effect" on the electrode material, reducing the direct contact between the positive electrode material and the electrolyte, reducing side reactions, and improving the thickness expansion rate of the battery cell at high temperature, thereby reducing the thickness expansion rate of the battery cell and improving the stability and safety of the electrochemical device in a high temperature environment. When A / B is too large, oxygen and hydrogen elements will be coated on the surface of the conductive carbon black, resulting in a decrease in the conductivity of the conductive carbon black and an increase in the resistivity of the conductive agent.

[0015] In some specific embodiments, the conductive carbon black satisfies: 0.8≤A / B≤1.5.

[0016] In the above specific implementation, when the conductive carbon black satisfies: 0.8≤A / B≤1.5, the two work together to further optimize the conductive network constructed by the conductive carbon black, further improve the electron transmission efficiency, reduce the DC internal resistance of the electrochemical device, and reduce the energy loss during the charging and discharging process, thereby further improving the energy conversion efficiency of the electrochemical device. At the same time, the structural changes of the electrode material caused by high temperature are further reduced, the good contact state between the electrode material and the electrolyte is maintained, the expansion of the battery cell thickness is further suppressed, the expansion rate of the battery cell thickness is reduced, and the stability and safety of the electrochemical device in a high temperature environment are further improved.

[0017] In some specific embodiments, based on the total mass of the conductive carbon black, the conductive carbon black includes 0.05% to 0.3% of oxygen element, and / or the conductive carbon black includes 0.05% to 0.3% of hydrogen element.

[0018] In the above specific embodiments, when the conductive carbon black includes 0.05% to 0.3% of oxygen, and / or the conductive carbon black includes 0.05% to 0.3% of hydrogen, the oxygen-containing functional group can enhance the chemical adsorption between the conductive carbon black and the positive electrode active material, and promote the transfer of electrons from the conductive carbon black to the active material; the hydrogen-containing structure regulates the electron cloud distribution of the conductive carbon black to a certain extent, improves its intrinsic conductivity, and thus improves the energy conversion efficiency of the electrochemical device. At the same time, the oxygen element can participate in the formation of stable chemical bonds, help maintain the lattice structure of the electrode material, and resist lattice distortion caused by high temperature; the hydrogen element can assist in regulating the microenvironment around the electrode material through weak interactions such as hydrogen bonds, alleviate stress concentration caused by high temperature, and improve the stability and safety of the electrochemical device in a high temperature environment. The presence of hydrogen and oxygen elements means that the surface of carbon black contains polar functional groups, which can increase the repulsion between carbon black particles on the one hand, and increase the bonding between binder molecules and carbon black on the other hand, thereby improving the uniformity of carbon black dispersion, and thus optimizing the continuity of the conductive network formed by the conductive carbon black in the electrode, thereby improving the efficiency of electron transfer. In addition, the binder can better combine with the conductive agent, and the presence of volatiles can make the conductive agent more evenly distributed, which has a better "coating effect" on the positive electrode material, reducing the contact between the positive electrode active material and the electrolyte, thereby reducing side reactions and improving the high-temperature expansion of the battery cell.

[0019] In some specific embodiments, based on the total mass of the conductive carbon black, the conductive carbon black includes 0.08% to 0.15% of oxygen element, and / or the conductive carbon black includes 0.08% to 0.15% of hydrogen element.

[0020] In the above specific embodiments, when the conductive carbon black includes 0.08% to 0.15% of oxygen element, and / or the conductive carbon black includes 0.08% to 0.15% of hydrogen element, the energy conversion efficiency of the electrochemical device and the stability and safety of the electrochemical device in a high temperature environment can be further improved.

[0021] In some specific embodiments, the conductive carbon black satisfies at least one of the following conditions: (1) based on the total mass of the conductive carbon black, the conductive carbon black includes 100 ppb to 500 ppb of magnetic impurities; (2) based on the total mass of the conductive carbon black, the conductive carbon black includes 50 ppb to 500 ppb of ash; (3) the volatile matter loss temperature of the conductive carbon black is 550°C to 950°C; (4) the Dv50 of the conductive carbon black is 1000 nm to 6000 nm; (5) the average particle size of the carbon black unit is 30 nm to 70 nm; (6) the powder resistivity of the conductive carbon black is 25 mΩ·cm to 45 mΩ·cm; (7) the half-height width of the (002) crystal plane diffraction peak in the X-ray diffraction pattern of the conductive carbon black is 1° to 5°; (8) the infrared absorption spectrum of the conductive carbon black has a peak value of 1700 to 1730 cm -1 The peak at 2500~300cm -1 The ratio of the peak values ​​at is 0.2~0.7; (9) The conductive carbon black includes a plurality of carbon black units stacked to form a core and a plurality of branches connected to the core; (10) The Dv50 of the conductive carbon black is Cnm, the average particle size of the carbon black unit is Dnm, and the conductive carbon black satisfies: 25≤C / D≤150.

[0022] In the above specific embodiment, when the conductive carbon black includes 100ppb~500ppb of magnetic impurities, the internal structure of the electrochemical device can be kept stable, reducing the capacity loss caused by short circuit and other problems. At the same time, because the reduction potential of metal impurity ions is lower than that of lithium ions, during the charging process, the metal impurity ions will first be embedded in the carbon negative electrode, occupying the position where the lithium ions are embedded, reducing the reversible capacity of the lithium ion electrochemical device. During high-temperature cycling, this effect will gradually accumulate, causing the capacity of the electrochemical device to decay rapidly. When the conductive carbon black includes 100ppb~500ppb of magnetic impurities, lithium ions can be more fully embedded and removed during the charging and discharging process, reducing irreversible capacity loss, thereby improving the high-temperature cycle retention rate of the electrochemical device. When there are too many magnetic impurities, side reactions will occur in the electrochemical device during the cycle, reducing the cycle capacity retention rate.

[0023] When the conductive carbon black contains 50ppb~500ppb of ash, it can make the conductive carbon black particles contact better and form a more effective conductive network, so that the electron transmission of the electrochemical device is smoother during the charging and discharging process. During the high-temperature cycle process, the chemical reaction inside the electrochemical device is intense. Good conductivity helps to maintain the stable performance of the electrochemical device, reduce energy loss and heating of the electrochemical device caused by increased resistance, and at the same time, reduce the probability of side reactions. In a high-temperature environment, the impact of side reactions will be more significant. Reducing side reactions helps to maintain the stability of the chemical system inside the electrochemical device, so that the electrochemical device can still maintain a high capacity after multiple cycles, thereby improving the high-temperature cycle retention rate. When there is too much ash, side reactions will occur in the electrochemical device during the cycle, reducing the cycle capacity retention rate.

[0024] When the volatile loss temperature of conductive carbon black is 550℃~950℃, the conductive carbon black will not undergo significant changes in structure and performance due to the large loss of volatiles. Therefore, it can maintain its own morphology and conductivity, maintain a good conductive network inside the electrochemical device, ensure smooth electron transmission, and the volatiles are relatively stable within the operating temperature range of the electrochemical device, not easy to decompose or participate in other side reactions, which helps to improve the high-temperature cycle retention rate of the electrochemical device. When the volatile loss temperature is too high, the carbon chain where the functional group is located is longer, and the excessively long carbon chain leads to a reduced proportion of functional groups and uneven attachment, which makes the conductive carbon black poorly dispersed and easy to agglomerate. When the volatile loss temperature is too low, the carbon chain where the functional group is located is shorter, and decomposition reactions are prone to occur, thereby affecting the performance of the electrochemical device. When the Dv50 of conductive carbon black is 1000nm~6000nm, the conductive carbon black can form a relatively continuous conductive path in the electrode, which can make the path for electron transmission in it shorter and less resistant. When the electrochemical device is in high-rate discharge, it can meet the needs of rapid conduction of a large number of electrons, thereby improving the discharge rate performance of the electrochemical device and enabling the electrochemical device to release more electricity in a short time. At the same time, when the electrode material expands, the conductive carbon black particles can be squeezed and deformed to a certain extent, absorbing part of the thermal stress, thereby reducing the overall expansion of the electrode and reducing the thickness expansion rate of the battery cell.

[0025] When the average particle size of the carbon black unit is 30nm~70nm, the conductive carbon black can fully contact the electrode material and provide more conductive sites. This helps to form a dense conductive network inside the electrode, making the electron transmission path richer, thereby reducing the internal resistance of the electrochemical device. During high-rate discharge, electrons can be transmitted more quickly between the electrode material and the conductive carbon black, improving the discharge efficiency of the electrochemical device and thus improving the discharge rate performance. At the same time, it can be filled in the tiny pores and grain boundaries of the electrode material. During high-temperature storage, these fine carbon black particles can play a certain supporting role, limiting the thermal expansion and lattice changes of the electrode material particles, thereby inhibiting the overall expansion of the electrode and reducing the thickness expansion rate of the battery cell. If the average particle size of the carbon black unit is too small, the binder will be consumed, thereby increasing the high-temperature expansion rate of the battery cell. At the same time, if the average particle size of the carbon black unit is too small, it is easy to be unevenly dispersed, reducing the rate performance of the electrochemical device.

[0026] When the powder resistivity of conductive carbon black is 25mΩ·cm~45mΩ·cm, it can effectively reduce the overall resistance of the electrode, allowing electrons to be quickly transmitted in the electrode material, and increasing the rate of electrochemical reactions during charging and discharging. In addition, it helps to form a uniform electric field distribution inside the electrochemical device, which makes the electrochemical reaction on the electrode surface more uniform and avoids uneven reactions in local areas due to excessively high or low electric field strength. During high-temperature cycling, this uniform reaction is conducive to reducing local loss and polarization of electrode materials, extending the service life of the electrochemical device, and improving the high-temperature cycle retention rate of the electrochemical device.

[0027] When the half-height width of the (002) crystal plane diffraction peak in the X-ray diffraction spectrum of conductive carbon black is 1°~5°, the conductive carbon black surface has more active sites. During the charge and discharge process of the electrochemical device, these active sites can promote the electrochemical reaction between the electrode material and the electrolyte and increase the reaction rate. Under high-temperature cycle conditions, the internal chemical reaction rate of the electrochemical device is accelerated. More active sites help maintain a higher reaction efficiency, allowing the electrochemical device to charge and discharge more fully. At the same time, the conductive carbon black is better combined with the electrode material to enhance the interface adhesion. During the high-temperature cycle of the electrochemical device, the volume of the electrode material expands and contracts due to charge and discharge, and good combination can effectively buffer the stress caused by this volume change, reduce the shedding and pulverization of the electrode material, maintain the integrity of the electrode structure, and thus improve the high-temperature cycle retention rate of the electrochemical device. When the half-height width of the diffraction peak is too large, side reactions will occur in the electrochemical device during the cycle, reducing the cycle capacity retention rate. When the half-width of the diffraction peak is too small, the bonding ability between the conductive carbon black and the binder is weak, it is not easy to disperse, and it is easy to agglomerate, thereby reducing the coating of the conductive carbon black on the positive electrode active material and reducing the cycle capacity retention rate.

[0028] In the infrared absorption spectrum of conductive carbon black, the range of 1700~1730cm-1 The peak at 2500~300cm -1 When the ratio of the peaks at is 0.2~0.7, the conductive carbon black can interact with the electrode material through hydrogen bonding and other effects, thereby enhancing the electron transfer efficiency between the conductive carbon black and the electrode material. At the same time, it helps to form a good conductive channel and ion transfer path on the electrode surface, reduce the obstacles to electron and ion transfer, reduce the internal resistance of the electrochemical device, reduce the energy loss inside the electrochemical device, and thus improve the energy conversion efficiency of the electrochemical device. In addition, it helps to improve the interfacial compatibility between the electrode and the electrolyte. Functional groups such as hydroxyl groups can interact with certain components in the electrolyte, consume substances that may cause side reactions, inhibit the decomposition of the electrolyte at high temperature and the side reactions on the electrode surface, reduce gas production and heat generation, thereby reducing the internal pressure of the electrochemical device and inhibiting the expansion of the battery cell thickness.

[0029] When the conductive carbon black includes a plurality of carbon black units stacked to form a core and a plurality of branches connected to the core, the core is formed by stacking a plurality of carbon black units, which provides a main channel for electron transmission and can reduce the resistance of electron transmission. The branches are connected to the core, which increases the contact points and contact area between the conductive carbon black and the electrode material, so that electrons can be transmitted to various parts of the electrode material more quickly and efficiently through the branches, and the carbon black units are combined with each other to form a multi-branched structure with intermolecular bonding. The existence of the branched structure is conducive to a continuous conductive network, improves the efficiency of electron transmission, and reduces the resistance of electron transmission, thereby forming a more complete and efficient conductive network inside the electrochemical device. During high-temperature cycling, the chemical reaction rate inside the electrochemical device is accelerated, and the requirements for electron transmission efficiency are higher. This structure can ensure the rapid conduction of electrons, maintain the charge and discharge performance of the electrochemical device, and thus improve the high-temperature cycle retention rate.

[0030] When the conductive carbon black satisfies: 25≤C / D≤150, a multi-level structure with both large particles supporting and small particles densely filling can be formed. This structure is conducive to building a stable and efficient conductive network inside the electrode. The synergistic effect of the two can improve the liquid retention rate of the electrode, promote the transmission, adsorption and desorption of lithium ions, thereby reducing the internal resistance of the electrochemical device and increasing the discharge rate. In addition, it can reduce the agglomeration and deformation of the electrode material at high temperature, inhibit local overheating and the intensification of side reactions, thereby reducing the pressure inside the electrochemical device and inhibiting the thickness expansion of the battery cell. When C / D is too large, the interaction between the conductive carbon blacks is strong and it is not easy to disperse, which causes uneven dispersion of the conductive carbon black and affects the performance of the electrochemical device.

[0031] In some specific embodiments, the conductive carbon black satisfies at least one of the following conditions: (1) the Dv50 of the conductive carbon black is 1500nm~5000nm; (2) the average particle size of the carbon black unit is 40nm~60nm; (3) the powder resistivity of the conductive carbon black is 30mΩ·cm~40mΩ·cm; (4) the half-height width of the (002) crystal plane diffraction peak in the X-ray diffraction spectrum of the conductive carbon black is 1.5°~3°; (5) the infrared absorption spectrum of the conductive carbon black is 1700~1730cm -1 The peak at 2500~300cm -1 The ratio of the peak values ​​at is 0.3~0.6.

[0032] In the above specific embodiments, when the conductive carbon black satisfies any one of the conditions, the electron transfer efficiency between the conductive carbon black and the electrode material can be further improved, and the internal resistance of the positive electrode plate can be reduced, thereby further improving the cycle retention rate and energy conversion efficiency of the electrochemical device. In a second aspect, the present application provides a positive electrode plate, which includes a binder, positive electrode active material particles and a conductive agent, and the conductive agent includes the conductive carbon black and carbon nanotubes of the first aspect. The positive electrode plate has good lithium ion transmission and structural stability, thereby improving the performance of the electrochemical device.

[0033] In some specific embodiments, the positive electrode sheet satisfies at least one of the following conditions: (1) the specific surface area of ​​the conductive agent is Em 2 / g, based on the total mass of the positive electrode sheet, the positive electrode sheet includes W1% of the conductive agent and W2% of the binder, and the positive electrode sheet satisfies: 0.004×E×W1≤W2≤0.014×E×W1; (2) the specific surface area of ​​the conductive agent is 40 m 2 / g ~300 m 2 / g; (3) based on the total mass of the positive electrode sheet, the positive electrode sheet includes 0.5%~3% of the conductive agent; (4) based on the total mass of the positive electrode sheet, the positive electrode sheet includes 0.5%~5% of the binder; (5) the mass ratio of conductive carbon black to carbon nanotubes in the conductive agent is 0.6~2.

[0034] In the above specific embodiment, when the positive electrode sheet satisfies: 0.004×E×W1≤W2≤0.014×E×W1, the binder can better bond the conductive agent and the active material together, so that the conductive agent is evenly dispersed between the active materials to form an efficient conductive network. At the same time, an appropriate amount of binder will not block the electrode pores too much, ensuring the penetration of the electrolyte and the transmission channel of lithium ions, thereby reducing the internal resistance of the electrochemical device and increasing the discharge rate. It can also improve the interface compatibility between the electrode and the electrolyte, reduce the decomposition of the electrolyte at high temperature and the side reactions on the electrode surface. Good interface compatibility helps to reduce the reaction resistance on the electrode surface, make the reaction more uniform, and reduce local overheating and gas production. Reduced gas production can reduce the pressure inside the electrochemical device, thereby inhibiting the thickness expansion of the battery cell.

[0035] The specific surface area of ​​the conductive agent is 40 m 2 / g ~300 m 2 / g, the conductive agent has a richer pore structure and greater surface energy. The pore structure is conducive to the adsorption and storage of the electrolyte, providing more transmission channels for lithium ions, and accelerating the diffusion of lithium ions in the electrode material. The time for lithium ions to migrate from the inside of the active material to the surface is shortened, thereby increasing the supply rate of lithium ions in the electrochemical device during high-rate discharge and improving the discharge rate. At the same time, it can play a better supporting role between the active material particles and increase the stability of the electrode structure. Under high temperature conditions, the active material may undergo thermal expansion and structural changes, and the conductive agent, with its large specific surface area and good dispersibility, can limit the excessive movement and agglomeration of the active material particles, maintain the integrity of the electrode structure, and thus reduce the thickness expansion rate of the battery cell.

[0036] When the positive electrode sheet includes 0.5% to 3% of a conductive agent and / or 0.5% to 5% of a binder, the electrode porosity can be increased, which is beneficial to the penetration of the electrolyte and the diffusion of lithium ions. It works synergistically with the conductive network to increase the migration rate of lithium ions, thereby increasing the discharge rate of the electrochemical device. At the same time, the conductive agent and the binder can improve the interfacial properties between the electrode and the electrolyte. The binder prevents excessive contact between the electrolyte and the active material, inhibits the occurrence of side reactions, and the conductive agent promotes charge transfer on the electrode surface, making the reaction more uniform and reducing local overheating and gas production. The two work together to reduce the internal pressure of the electrochemical device, thereby inhibiting the expansion of the battery cell thickness.

[0037] When the mass ratio of conductive carbon black and carbon nanotubes in the conductive agent is 0.6-2, the synergistic effect of the two helps to optimize the pore structure and surface properties inside the electrode. The porous structure of conductive carbon black can absorb more electrolyte, providing abundant transmission channels and storage sites for lithium ions. The presence of carbon nanotubes can further guide the transmission direction of lithium ions, making them diffuse more quickly and evenly in the electrode material. Therefore, during the charge and discharge process, lithium ions can be more efficiently embedded and extracted between the active material and the electrolyte, thereby improving the discharge rate of the electrochemical device. In addition, under high temperature conditions, the synergistic effect of conductive carbon black and carbon nanotubes can enhance the stability of the electrode structure. Conductive carbon black can be filled between the active material particles to play a buffering and supporting role, reducing the mutual extrusion and deformation of the active material particles due to thermal expansion. Carbon nanotubes can be interspersed in the entire electrode structure like a "skeleton", improving the overall mechanical strength of the electrode and limiting the displacement and agglomeration of the active material particles. The synergistic effect of the two can form a stable three-dimensional structure, effectively inhibiting the expansion and deformation of the electrode at high temperature, thereby reducing the thickness expansion rate of the battery cell.

[0038] In some specific embodiments, the positive electrode sheet satisfies at least one of the following conditions: (1) the positive electrode sheet satisfies: 0.007×E×W1≤W2≤0.012×E×W1; (2) the specific surface area of ​​the conductive agent is 100m 2 / g~200m 2 / g; (3) based on the total mass of the positive electrode sheet, the positive electrode sheet includes 0.8%~2.5% of the conductive agent; (4) based on the total mass of the positive electrode sheet, the positive electrode sheet includes 1.0%~3.0% of the binder; (5) the mass ratio of conductive carbon black to carbon nanotubes in the conductive agent is 0.8~1.5.

[0039] In the above specific embodiments, when the positive electrode sheet satisfies at least one of the above items, the discharge rate of the electrochemical device can be increased and the thickness expansion rate of the battery cell can be reduced.

[0040] In a third aspect, the present application provides an electrochemical device, which includes the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte of the second aspect. The electrochemical device has a low internal resistance and a high temperature storage cell thickness expansion rate, and also has a high high temperature cycle capacity retention rate and charge and discharge performance.

[0041] In some specific embodiments, the electrochemical device satisfies at least one of the following conditions: (1) based on the total mass of the electrolyte, the electrolyte includes Z% of the dinitrile additive, and the specific surface area of ​​the conductive agent is Em 2 / g, the electrochemical device satisfies: 50≤E / Z≤1000; (2) based on the total mass of the electrolyte, the electrolyte includes 0.5%~5% of 2,2-difluoroethyl acetate; (3) the Dv50 of the positive electrode active material particles is Gμm, based on the total mass of the electrolyte, the electrolyte includes X% of propyl propionate, and the electrochemical device satisfies: 2≤G / X≤5; (5) the Dv50 of the positive electrode active material particles is 5μm~25μm; (4) based on the total mass of the electrolyte, the electrolyte includes 5%~30% of propyl propionate.

[0042] In the above specific embodiment, when the electrochemical device satisfies: 14.2≤E / Z≤7500, the dinitrile additive can form a stable solid electrolyte interface (SEI) film on the electrode surface, which can prevent further reaction between the electrolyte and the electrode material, reduce corrosion and dissolution of the electrode material, and thus improve the cycle stability of the electrochemical device. The high specific surface area of ​​conductive carbon black helps to evenly distribute the active substances on the electrode surface, reduce the agglomeration and shedding of the active substances, and is also conducive to the uniform formation of the SEI film, ensuring the synergistic effect of the additive and conductive carbon black in improving the cycle stability, so that the electrochemical device can still maintain good performance after multiple charge and discharge cycles. In addition, the synergistic effect of the two makes the charge transfer inside the electrochemical device more efficient and the charge and discharge process smoother.

[0043] When the electrolyte includes 0.02% to 12.5% ​​2,2-difluoroethyl acetate, it helps to maintain the fluidity of the electrolyte in a low temperature environment, allowing ions to be more smoothly transmitted inside the electrochemical device, thereby improving the charge and discharge efficiency and capacity of the electrochemical device at low temperatures, and reducing the performance degradation of the electrochemical device at low temperatures. At the same time, the additive can form a stable solid electrolyte interface (SEI) film on the electrode surface. This film can prevent side reactions between the electrolyte and the electrode material, reduce the corrosion and dissolution of the electrode material, and inhibit the loss of active substances, thereby improving the cycle life of the electrochemical device, so that the electrochemical device can still maintain good performance after multiple charge and discharge cycles. However, too much 2,2-difluoroethyl acetate causes the electrolyte conductivity to decrease, making the CEI film loose, thereby reducing the cycle performance and rate performance of the electrochemical device.

[0044] When the electrochemical device satisfies: 0.125≤G / X≤0.83, it helps to achieve a good match between the positive electrode active material particles and the propyl propionate in the electrolyte. Propyl propionate can better infiltrate the surface of the active material particles, increase the contact area between the electrode and the electrolyte, facilitate the transmission of ions at the interface, reduce the interface resistance, and thus improve the charge and discharge efficiency of the electrochemical device. G / X that is too small will dilute the Li in the electrolyte. +The content will reduce the conductivity of the electrochemical device, and the formed CEI film will be loose and too thick, thereby reducing the cycle performance and rate performance of the electrochemical device.

[0045] In a fourth aspect, the present application provides an electronic device, which includes the electrochemical device of the third aspect. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0047] As used in this application, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.

[0048] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0049] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0050] With the booming development of electronic equipment and new energy vehicle industries, lithium battery performance faces extremely stringent requirements. However, in actual working conditions, lithium batteries have exposed many disadvantages in different environments and working conditions. For example, energy waste during charging and discharging, and voltage drops caused by internal resistance in scenarios such as electric vehicle startup that have high requirements for instantaneous high current output, seriously affect power output performance and reduce equipment operation stability.

[0051] Therefore, how to effectively solve the problem of low energy conversion efficiency of lithium batteries has become the key to improving the comprehensive performance of lithium batteries.

[0052] Based on the above problems, the embodiments of the present application provide a conductive carbon black, a positive electrode plate, an electrochemical device and an electronic device. The conductive carbon black can construct an efficient conductive network in the positive electrode plate, reduce the resistance of the positive electrode plate, and thus improve the energy conversion efficiency of the electrochemical device.

[0053] The following is a detailed description of the implementation of the present application.

[0054] Conductive carbon black The present invention provides a conductive carbon black, which includes a plurality of carbon black units and pores between adjacent carbon black units; the carbon black unit in the present invention refers to a single ball constituting dendritic carbon black. Based on the total mass of the conductive carbon black, the volatile matter in the conductive carbon black is M%, and the specific surface area of ​​the conductive carbon black is Nm 2 / g, conductive carbon black satisfies: 0.003≤M / N≤0.02.

[0055] For example, M / N may be 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016, 0.017, 0.018, 0.019, 0.02, or a range consisting of any of the above values.

[0056] Optional, 0.005≤M / N≤0.02, 0.005≤M / N≤0.018, 0.005≤M / N≤0.016, 0.005≤M / N≤0.014, 0.005≤M / N≤0.012, 0.005≤M / N≤0.01.

[0057] According to the present application, when the conductive carbon black of the present application is used and the conductive carbon black satisfies 0.003≤M / N≤0.02, the conductive carbon black can construct an efficient conductive network in the positive electrode sheet. On the one hand, it can reduce the DC internal resistance of the electrochemical device, make the electron transmission smoother, reduce the energy loss during the charging and discharging process, and improve the energy conversion efficiency of the electrochemical device. On the other hand, it can enhance the interaction between the conductive carbon black and the electrode material, improve the structural stability of the electrode material, reduce the structural changes caused by high temperature, maintain a good contact state between the electrode material and the electrolyte, and thus inhibit the expansion of the battery cell thickness. In addition, the thickness expansion rate of the battery cell is reduced, and the stability and safety of the electrochemical device in a high temperature environment are improved.

[0058] In some specific embodiments, based on the total mass of the conductive carbon black, the mass percentage of volatile matter in the conductive carbon black is 0.1% to 0.7%, and / or the specific surface area of ​​the conductive carbon black is 30 m 2 / g~80m 2 / g.

[0059] For example, the volatile matter content in the conductive carbon black can be 0.1%, 0.15%, 0.12%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, or a range consisting of any of the above values.

[0060] The specific surface area of ​​conductive carbon black can be 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g, 50m 2 / g, 55m 2 / g, 60m 2 / g, 65m 2 / g, 70m 2 / g, 75m 2 / g, 80m 2 / g, or any range consisting of the above values.

[0061] Optionally, the volatile matter content in the conductive carbon black can be 0.15%~0.7%, 0.2%~0.7%, 0.25%~0.7%, 0.3%~0.7%, 0.3%~0.65%, 0.3%~0.6%.

[0062] Optionally, the conductive carbon black may have a specific surface area of ​​35 m 2 / g~80m 2 / g,40m 2 / g~80m 2 / g,45m 2 / g~80m 2 / g,50m 2 / g~80m 2 / g,50m 2 / g~75m 2 / g,50m 2 / g~70m 2 / g.

[0063] In the above specific embodiments, the volatile matter in the conductive carbon black is 0.1% to 0.7%, and / or the specific surface area of ​​the conductive carbon black is 30 m 2 / g~80m 2 / g, electrons can more efficiently flow from the external circuit into the positive electrode active material to participate in the electrochemical reaction, or flow out from the positive electrode active material to the external circuit, reducing energy loss, thereby improving the energy conversion efficiency of the electrochemical device. At the same time, it can adjust the microenvironment around the conductive carbon black and the electrode material. Then, the influence of high temperature on the structure of the electrode material is alleviated, so that the electrode material and the electrolyte maintain a good contact state. When the structure inside the battery cell changes due to high temperature, the presence of volatiles helps to stabilize the lattice structure of the electrode material and inhibit the lattice distortion caused by high temperature, thereby effectively reducing the thickness expansion rate of the battery cell and improving the stability and safety of the electrochemical device in a high temperature environment. When the specific surface area of ​​the conductive carbon black is too small, the effective conductive area is reduced, thereby increasing the DC internal resistance of the electrochemical device, and causing the dispersion effect of the conductive carbon black to deteriorate, reducing the coating of the positive electrode active material, thereby increasing the thickness expansion rate of the battery cell.

[0064] In some specific embodiments, based on the total mass of the conductive carbon black, the conductive carbon black includes A% of oxygen elements, the conductive carbon black includes B% of hydrogen elements, and the conductive carbon black satisfies: 0.5≤A / B≤2.

[0065] For example, A / B may be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, or a range consisting of any of the above values.

[0066] Optional, 0.6≤A / B≤2, 0.7≤A / B≤2, 0.8≤A / B≤2, 0.8≤A / B≤1.9, 0.8≤A / B≤1.8, 0.8≤A / B≤1.7, 0.8≤A / B≤1.6, 0.8≤A / B≤1.5.

[0067] In the above specific embodiments, when the conductive carbon black satisfies: 0.5≤A / B≤2, the chemical properties of the surface of the conductive carbon black can be optimized. The oxygen-containing functional groups and hydrogen-containing structures on the surface of the conductive carbon black are adjusted. The two work synergistically to optimize the conductive network constructed by the conductive carbon black, improve the electron transmission efficiency, reduce the DC internal resistance of the electrochemical device, and reduce the energy loss during the charging and discharging process, thereby improving the energy conversion efficiency of the electrochemical device. At the same time, the stabilizing effect of the conductive carbon black on the structure of the electrode material can be enhanced. The two work synergistically to reduce the structural changes of the electrode material caused by high temperature, maintain a good contact state between the electrode material and the electrolyte, effectively inhibit the expansion of the battery cell thickness, and then reduce the thickness expansion rate of the battery cell, and improve the stability and safety of the electrochemical device in a high temperature environment. When A / B is too large, oxygen and hydrogen elements will be coated on the surface of the conductive carbon black, resulting in a decrease in the conductivity of the conductive carbon black and an increase in the resistivity of the conductive agent.

[0068] It should be noted that the oxygen content and hydrogen content of the conductive carbon black can be detected using methods and instruments known in the art. For example, the electrochemical device can be disassembled to obtain the positive electrode plate, and then the conductive carbon black can be further disassembled. Using the element analyzer method, an appropriate amount of the conductive carbon black sample is weighed and placed in the sample boat of the element analyzer. Then, the sample boat is sent to the combustion furnace, and the sample undergoes a combustion reaction under the action of high temperature and oxygen flow. The combustion products pass through a series of separation and detection devices, such as detecting the water generated by the conversion of hydrogen elements through the desiccant absorbing moisture, and detecting the carbon dioxide generated by the conversion of oxygen elements through the carbon dioxide absorbent. The instrument automatically calculates and displays the content of hydrogen and oxygen elements according to the absorption amount.

[0069] In some specific embodiments, based on the total mass of the conductive carbon black, the conductive carbon black includes 0.05% to 0.3% of oxygen element, and / or the conductive carbon black includes 0.05% to 0.3% of hydrogen element.

[0070] For example, the content of oxygen in the conductive carbon black can be 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, or a range consisting of any of the above values.

[0071] The content of hydrogen in the conductive carbon black can be 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, or a range consisting of any of the above values.

[0072] Optionally, the content of oxygen in the conductive carbon black can be 0.08%~0.3%, 0.08%~0.28%, 0.08%~0.25%, 0.08%~0.22%, 0.08%~0.2%, 0.08%~0.18%, 0.08%~0.15%.

[0073] Optionally, the content of hydrogen in the conductive carbon black can be 0.08%~0.3%, 0.08%~0.28%, 0.08%~0.25%, 0.08%~0.22%, 0.08%~0.2%, 0.08%~0.18%, 0.08%~0.15%.

[0074] In the above specific embodiments, when the conductive carbon black includes 0.05% to 0.3% of oxygen, and / or the conductive carbon black includes 0.05% to 0.3% of hydrogen, the oxygen-containing functional group can enhance the chemical adsorption between the conductive carbon black and the positive electrode active material, and promote the transfer of electrons from the conductive carbon black to the active material; the hydrogen-containing structure regulates the electron cloud distribution of the conductive carbon black to a certain extent, improves its intrinsic conductivity, and thus improves the energy conversion efficiency of the electrochemical device. At the same time, the oxygen element can participate in the formation of stable chemical bonds, help maintain the lattice structure of the electrode material, and resist lattice distortion caused by high temperature; the hydrogen element can assist in regulating the microenvironment around the electrode material through weak interactions such as hydrogen bonds, alleviate stress concentration caused by high temperature, and improve the stability and safety of the electrochemical device in a high temperature environment.

[0075] In some specific embodiments, the conductive carbon black satisfies at least one of the following conditions: (1) based on the total mass of the conductive carbon black, the conductive carbon black includes 100 ppb to 500 ppb of magnetic impurities, for example, the content of magnetic impurities in the conductive carbon black is 100 ppb, 150 ppb, 200 ppb, 250 ppb, 300 ppb, 350 ppb, 400 ppb, 450 ppb, 500 ppb, or a range consisting of any of the above values; (2) based on the total mass of the conductive carbon black, the conductive carbon black includes 50 ppb to 500 ppb of ash, for example, the content of ash in the conductive carbon black can be 50 ppb, 100 ppb, 150 ppb, 200 ppb, 250 ppb, 300 ppb, 350 ppb, 400 ppb, 450 ppb, 500 ppb, or a range consisting of any of the above values. 0ppb, 350ppb, 400ppb, 450ppb, 500ppb, or a range consisting of any of the above values; (3) the volatile loss temperature of the conductive carbon black is 550°C to 950°C, for example, it can be 550°C, 580°C, 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, or a range consisting of any of the above values; (4) the Dv50 of the conductive carbon black is 1000nm to 6000nm, for example, it can be 1000nm, 1200nm, 1500nm, 1800nm, 2000nm , 2200nm, 2500nm, 2800nm, 3000nm, 3200nm, 3500nm, 3800nm, 4000nm, 4200nm, 4500nm, 4800nm, 5000nm, 5200nm, 5500nm, 5800nm, 6000nm, or any range consisting of the above values; (5) the average particle size of the carbon black unit is 30nm to 70nm, for example, 30nm, 32nm, 35nm, 38nm, 40nm, 42nm, 45nm, 48nm, 50nm, 52nm, 55nm, 58nm, 60nm, 62nm, 65nm, 68nm, 70nm, or any range consisting of the above values. (6) the powder resistivity of the conductive carbon black is 25 mΩ·cm to 45 mΩ·cm, for example, 25 mΩ·cm, 28 mΩ·cm, 30 mΩ·cm, 32 mΩ·cm, 35 mΩ·cm, 38 mΩ·cm, 40 mΩ·cm, 42 mΩ·cm, 45 mΩ·cm, or any range thereof; (7) the half-width at half-maximum of the (002) crystal plane diffraction peak in the X-ray diffraction pattern of the conductive carbon black is 1° to 5°, for example, 1°, 1.2°, 1.5°, 1.8°, 2°, 2.2°, 2.5°, 2.8°, 3°, 3.2°, 3.5°, 3.8°, 4°, 4.2°, 4.5°, 4.8°, 5°, or any of the above values; (8) 1700~1730cm in the infrared absorption spectrum of conductive carbon black. -1 The peak at 2500~300cm -1 The ratio of the peak values ​​at is 0.2 to 0.7, for example, 0.2, 0.22, 0.25, 0.28, 0.3, 032, 0.35, 0.38, 0.4, 0.42, 0.45, 0.48, 0.5, 0.52, 0.55, 0.58, 0.6, 0.62, 0.65, 0.68, 0.7, or any range thereof; (9) The conductive carbon black comprises a plurality of carbon black units stacked to form a core and a plurality of connecting units. on the branches on the core; (10) the Dv50 of the conductive carbon black is Cnm, the average particle size of the carbon black unit is Dnm, and the conductive carbon black satisfies: 25≤C / D≤150, for example, it can be 25, 30, 35, 40, 45, 50, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, or a range consisting of any of the above values.

[0076] Optionally, the Dv50 of the conductive carbon black can be 1300nm~3000nm, 1500nm~6000nm, 1500nm~5800nm, 1500nm~5600nm, 1500nm~5400nm, 1500nm~5200nm, 1500nm~5000nm.

[0077] Optionally, the average particle size of the carbon black unit can be 32nm~70nm, 35nm~70nm, 38nm~70nm, 40nm~70nm, 40nm~68nm, 40nm~65nm, 40nm~62nm, 40nm~60nm.

[0078] Optionally, the powder resistivity of the conductive carbon black may be 28mΩ·cm~45mΩ·cm, 30mΩ·cm~45mΩ·cm, 30mΩ·cm~44mΩ·cm, 30mΩ·cm~43mΩ·cm, 30mΩ·cm~42mΩ·cm, 30mΩ·cm~41mΩ·cm, 30mΩ·cm~40mΩ·cm.

[0079] Optionally, the half-width of the (002) crystal plane diffraction peak in the X-ray diffraction pattern of the conductive carbon black can be 1.2°~5°, 1.5°~5°, 1.5°~4.8°, 1.5°~4.5°, 1.5°~4.2°, 1.5°~4°, 1.5°~3.8°, 1.5°~3.5°, 1.5°~3.2°, 1.5°~3°.

[0080] Optionally, the ratio of the peak value at 1700~1730cm-1 to the peak value at 2500~300cm-1 in the infrared absorption spectrum of the conductive carbon black is 0.22~0.7, 0.25~0.7, 0.28~0.7, 0.3~0.7, 0.3~0.68, 0.3~0.65, 0.3~0.62, 0.3~0.6.

[0081] In the above specific embodiments, when the conductive carbon black includes 100ppb~500ppb of magnetic impurities, the internal structure of the electrochemical device can be kept stable, reducing the capacity loss caused by short circuits and other problems. At the same time, because the reduction potential of metal impurity ions is lower than that of lithium ions, during the charging process, the metal impurity ions will first be embedded in the carbon negative electrode, occupying the position where the lithium ions are embedded, reducing the reversible capacity of the lithium ion electrochemical device. During high-temperature cycling, this effect will gradually accumulate, causing the capacity of the electrochemical device to decay rapidly. When the conductive carbon black includes 100ppb~500ppb of magnetic impurities, lithium ions can be more fully embedded and removed during the charging and discharging process, reducing irreversible capacity loss, thereby improving the high-temperature cycle retention rate of the electrochemical device. When there are too many magnetic impurities, side reactions will occur in the electrochemical device during the cycle, reducing the cycle capacity retention rate.

[0082] When the conductive carbon black contains 50ppb~500ppb of ash, it can make the conductive carbon black particles contact better and form a more effective conductive network, so that the electron transmission of the electrochemical device is smoother during the charging and discharging process. During the high-temperature cycle process, the chemical reaction inside the electrochemical device is intense. Good conductivity helps to maintain the stable performance of the electrochemical device, reduce energy loss and heating of the electrochemical device caused by increased resistance, and at the same time, reduce the probability of side reactions. In a high-temperature environment, the impact of side reactions will be more significant. Reducing side reactions helps to maintain the stability of the chemical system inside the electrochemical device, so that the electrochemical device can still maintain a high capacity after multiple cycles, thereby improving the high-temperature cycle retention rate. When there is too much ash, side reactions will occur in the electrochemical device during the cycle, reducing the cycle capacity retention rate.

[0083] When the volatile loss temperature of conductive carbon black is 550℃~950℃, the conductive carbon black will not undergo significant changes in structure and performance due to the large loss of volatiles. Therefore, it can maintain its own morphology and conductivity, maintain a good conductive network inside the electrochemical device, ensure smooth electron transmission, and the volatiles are relatively stable within the operating temperature range of the electrochemical device, not easy to decompose or participate in other side reactions, which helps to improve the high-temperature cycle retention rate of the electrochemical device. When the volatile loss temperature is too high, the carbon chain where the functional group is located is longer, and the excessively long carbon chain leads to a reduced proportion of functional groups and uneven attachment, which makes the conductive carbon black poorly dispersed and easy to agglomerate. When the volatile loss temperature is too low, the carbon chain where the functional group is located is shorter, and decomposition reactions are prone to occur, thereby affecting the performance of the electrochemical device. When the Dv50 of conductive carbon black is 1000nm~6000nm, the conductive carbon black can form a relatively continuous conductive path in the electrode, which can make the path for electron transmission in it shorter and less resistant. When the electrochemical device is in high-rate discharge, it can meet the needs of rapid conduction of a large number of electrons, thereby improving the discharge rate performance of the electrochemical device and enabling the electrochemical device to release more electricity in a short time. At the same time, when the electrode material expands, the conductive carbon black particles can be squeezed and deformed to a certain extent, absorbing part of the thermal stress, thereby reducing the overall expansion of the electrode and reducing the thickness expansion rate of the battery cell.

[0084] When the average particle size of the carbon black unit is 30nm~70nm, the conductive carbon black can fully contact the electrode material and provide more conductive sites. This helps to form a dense conductive network inside the electrode, making the electron transmission path richer, thereby reducing the internal resistance of the electrochemical device. During high-rate discharge, electrons can be transmitted more quickly between the electrode material and the conductive carbon black, improving the discharge efficiency of the electrochemical device and thus improving the discharge rate performance. At the same time, it can be filled in the tiny pores and grain boundaries of the electrode material. During high-temperature storage, these fine carbon black particles can play a certain supporting role, limiting the thermal expansion and lattice changes of the electrode material particles, thereby inhibiting the overall expansion of the electrode and reducing the thickness expansion rate of the battery cell. If the average particle size of the carbon black unit is too small, the binder will be consumed, thereby increasing the high-temperature expansion rate of the battery cell. At the same time, if the average particle size of the carbon black unit is too small, it is easy to be unevenly dispersed, reducing the rate performance of the electrochemical device.

[0085] When the powder resistivity of conductive carbon black is 25mΩ·cm~45mΩ·cm, it can effectively reduce the overall resistance of the electrode, allowing electrons to be quickly transmitted in the electrode material, and increasing the rate of electrochemical reactions during charging and discharging. In addition, it helps to form a uniform electric field distribution inside the electrochemical device, which makes the electrochemical reaction on the electrode surface more uniform and avoids uneven reactions in local areas due to excessively high or low electric field strength. During high-temperature cycling, this uniform reaction is conducive to reducing local loss and polarization of electrode materials, extending the service life of the electrochemical device, and improving the high-temperature cycle retention rate of the electrochemical device.

[0086] When the half-height width of the (002) crystal plane diffraction peak in the X-ray diffraction spectrum of conductive carbon black is 1°~5°, the conductive carbon black surface has more active sites. During the charge and discharge process of the electrochemical device, these active sites can promote the electrochemical reaction between the electrode material and the electrolyte and increase the reaction rate. Under high-temperature cycle conditions, the internal chemical reaction rate of the electrochemical device is accelerated. More active sites help maintain a higher reaction efficiency, allowing the electrochemical device to charge and discharge more fully. At the same time, the conductive carbon black is better combined with the electrode material to enhance the interface adhesion. During the high-temperature cycle of the electrochemical device, the volume of the electrode material expands and contracts due to charge and discharge, and good combination can effectively buffer the stress caused by this volume change, reduce the shedding and pulverization of the electrode material, maintain the integrity of the electrode structure, and thus improve the high-temperature cycle retention rate of the electrochemical device. When the half-height width of the diffraction peak is too large, side reactions will occur in the electrochemical device during the cycle, reducing the cycle capacity retention rate. When the half-width of the diffraction peak is too small, the bonding ability between the conductive carbon black and the binder is weak, it is not easy to disperse, and it is easy to agglomerate, thereby reducing the coating of the conductive carbon black on the positive electrode active material and reducing the cycle capacity retention rate.

[0087] In the infrared absorption spectrum of conductive carbon black, the range of 1700~1730cm -1 The peak at 2500~300cm -1 When the ratio of the peaks at is 0.2~0.7, the conductive carbon black can interact with the electrode material through hydrogen bonding and other effects, thereby enhancing the electron transfer efficiency between the conductive carbon black and the electrode material. At the same time, it helps to form a good conductive channel and ion transfer path on the electrode surface, reduce the obstacles to electron and ion transfer, reduce the internal resistance of the electrochemical device, reduce the energy loss inside the electrochemical device, and thus improve the energy conversion efficiency of the electrochemical device. In addition, it helps to improve the interfacial compatibility between the electrode and the electrolyte. Functional groups such as hydroxyl groups can interact with certain components in the electrolyte, consume substances that may cause side reactions, inhibit the decomposition of the electrolyte at high temperature and the side reactions on the electrode surface, reduce gas production and heat generation, thereby reducing the internal pressure of the electrochemical device and inhibiting the expansion of the battery cell thickness.

[0088] When the conductive carbon black includes a plurality of carbon black units stacked to form a core and a plurality of branches connected to the core, the core is composed of a plurality of carbon black units stacked, which provides a main channel for electron transmission and can reduce the resistance of electron transmission. The branches are connected to the core, which increases the contact points and contact area between the conductive carbon black and the electrode material, so that electrons can be transmitted to various parts of the electrode material more quickly and efficiently through the branches, thereby forming a more complete and efficient conductive network inside the electrochemical device. During high-temperature cycling, the chemical reaction rate inside the electrochemical device accelerates, and the requirements for electron transmission efficiency are higher. This structure can ensure the rapid conduction of electrons, maintain the charge and discharge performance of the electrochemical device, and thus improve the high-temperature cycle retention rate.

[0089] When the conductive carbon black satisfies: 25≤C / D≤150, a multi-level structure with both large particles supporting and small particles densely filling can be formed. This structure is conducive to building a stable and efficient conductive network inside the electrode. The synergistic effect of the two can promote the adsorption and desorption of lithium ions, thereby reducing the internal resistance of the electrochemical device and increasing the discharge rate. In addition, it can reduce the agglomeration and deformation of electrode materials at high temperatures, inhibit local overheating and the intensification of side reactions, thereby reducing the pressure inside the electrochemical device and inhibiting the thickness expansion of the battery cell. When C / D is too large, the interaction between the conductive carbon blacks is strong and it is not easy to disperse, which causes uneven dispersion of the conductive carbon black and affects the performance of the electrochemical device.

[0090] It should be noted that the magnetic impurity content, ash content, volatile matter loss temperature, Dv50, powder resistivity, average particle size of carbon black unit, half-width of the (002) crystal plane diffraction peak in the X-ray diffraction spectrum of conductive carbon black, and the infrared absorption spectrum of conductive carbon black at 1700~1730cm -1 The peak at 2500~300cm -1The ratio of the peaks at and the morphology of the conductive carbon black can be detected using methods and instruments known in the art. For example, the electrochemical device can be disassembled to obtain the positive pole piece and then further disassembled to obtain the conductive carbon black. The vibrating sample magnetometer method (VSM) is used to place the sample in the measurement system of the VSM and set appropriate measurement parameters, such as the magnetic field intensity range, vibration frequency, etc. The instrument will automatically measure the magnetic moment of the sample under different magnetic field intensities and draw a hysteresis loop. According to the characteristic parameters of the hysteresis loop, such as saturation magnetization, etc., combined with the magnetization characteristics of known magnetic impurities, the content of magnetic impurities is calculated through a specific algorithm. Using the high-temperature calcination method, the crucible containing the sample is placed in a high-temperature furnace, gradually heated to (815±10)℃, and calcined at this temperature until the sample is completely ashed to obtain the total mass of ash. Using thermogravimetric analysis (TGA), weigh the prepared conductive carbon black sample and put it into a crucible. Put the crucible with the sample into the thermogravimetric analyzer again, and heat it at the same heating rate as the blank test to obtain a thermogravimetric curve (TG curve) and a differential thermogravimetric curve (DTG curve). Combined with the TG and DTG curves, the temperature range of the loss of volatile matter of conductive carbon black can be determined. The Dv50 of conductive carbon black can be measured by a laser particle size analyzer. Using the two-electrode method, two electrodes are inserted into the sample cell to make good contact with the conductive carbon black powder. The distance between the electrodes needs to be accurately measured and recorded. The resistivity of the sample is measured using a resistivity tester to calculate the powder resistivity of the conductive carbon black. Using the electron microscope method, the conductive carbon black sample is evenly dispersed on the sample stage. For example, the sample can be ultrasonically dispersed in a solvent such as ethanol, and then dropped on a stage such as a copper mesh. After the solvent evaporates, it is placed in an electron microscope for observation. The particle size of multiple particles is measured by the measurement tool provided by the microscope, and then the average particle size of the carbon black unit and the morphology of the conductive carbon black are obtained by statistical analysis. The X-ray diffraction spectrum of conductive carbon black was obtained by XRD measurement, and the half-height width of the (002) crystal plane diffraction peak in the X-ray diffraction spectrum of conductive carbon black was obtained. The infrared absorption spectrum of conductive carbon black was obtained by Fourier transform infrared spectrometer, and the infrared absorption spectrum of conductive carbon black was analyzed based on the 1700~1730cm -1 The peak at 2500~300cm -1 The ratio of the peak values ​​at .

[0091] Positive electrode The embodiment of the present application provides a positive electrode plate, which includes a binder, positive active material particles and a conductive agent, wherein the conductive agent includes the above-mentioned conductive carbon black and carbon nanotubes. The positive electrode plate has good lithium ion transmission and structural stability, thereby improving the performance of the electrochemical device.

[0092] In some specific embodiments, the positive electrode sheet satisfies at least one of the following conditions: (1) the specific surface area of ​​the conductive agent is Em 2 / g, based on the total mass of the positive electrode sheet, the positive electrode sheet includes W1% of the conductive agent and W2% of the binder, and the positive electrode sheet satisfies: 0.004×E×W1≤W2≤0.014×E×W1 For example, E×W1 / W2 can be 0.004, 0.006, 0.008, 0.010, 0.012, 0.014, or a range consisting of any of the above values; (2) The specific surface area of ​​the conductive agent is 40m 2 / g~300m 2 / g, for example, the specific surface area of ​​the conductive agent can be 40m 2 / g, 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g, or any range consisting of the above values; (3) Based on the total mass of the positive electrode sheet, the positive electrode sheet includes 0.5% to 3% of the conductive agent, for example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, or any range consisting of the above values; (4) Based on the total mass of the positive electrode sheet, the positive electrode sheet includes 0.5% to 5% of the binder, for example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, or any range thereof; (5) the mass ratio of the conductive carbon black to the carbon nanotubes in the conductive agent is 0.6-2, for example, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, or any range thereof.

[0093] Optionally, 0.005×E×W1≤W2≤0.014×E×W1, 0.006×E×W1≤W2≤0.014×E×W1, 0.007×E×W1≤W2≤0.014×E×W1, 0.005×E×W1≤W2≤0.013×E×W1, 0.007×E×W1≤W2≤0.012×E×W1.

[0094] Optionally, the specific surface area of ​​the conductive agent can be 60m 2 / g~300m 2 / g,80m 2 / g~300m2 / g,100m 2 / g~300m 2 / g,100m 2 / g~280m 2 / g,100m 2 / g~260m 2 / g,100m 2 / g~240m 2 / g,100m 2 / g~220m 2 / g,100m 2 / g~200m 2 / g.

[0095] Optionally, the content of the conductive agent can be 0.6%~3%, 0.7%~3%, 0.8%~3%, 0.8%~2.9%, 0.8%~2.8%, 0.8%~2.7%, 0.8%~2.6%, 0.8%~2.5%.

[0096] Optionally, the content of the binder can be 0.8%~5%, 1%~5%, 1%~4.8%, 1%~4.5%, 1%~4.2%, 1%~4%, 1%~3.8%, 1%~3.5%, 1%~3.2%, 1%~3%.

[0097] In the above specific embodiment, when the positive electrode sheet satisfies: 0.004×E×W1≤W2≤0.014×E×W1, the binder can better bond the conductive agent and the active material together, so that the conductive agent is evenly dispersed between the active materials to form an efficient conductive network. At the same time, an appropriate amount of binder will not block the electrode pores too much, ensuring the penetration of the electrolyte and the transmission channel of lithium ions, thereby reducing the internal resistance of the electrochemical device and improving the discharge rate. It can also improve the interface compatibility between the electrode and the electrolyte, reduce the decomposition of the electrolyte at high temperature and the side reactions on the electrode surface. Good interface compatibility helps to reduce the reaction resistance on the electrode surface, make the reaction more uniform, and reduce local overheating and gas production. Reduced gas production can reduce the pressure inside the electrochemical device, thereby inhibiting the thickness expansion of the battery cell.

[0098] The specific surface area of ​​the conductive agent is 40m 2 / g ~300m 2 / g, the conductive agent has a richer pore structure and greater surface energy. The pore structure is conducive to the adsorption and storage of the electrolyte, providing more transmission channels for lithium ions, and accelerating the diffusion of lithium ions in the electrode material. The time for lithium ions to migrate from the inside of the active material to the surface is shortened, thereby increasing the supply rate of lithium ions in the electrochemical device during high-rate discharge and improving the discharge rate. At the same time, it can play a better supporting role between the active material particles and increase the stability of the electrode structure. Under high temperature conditions, the active material may undergo thermal expansion and structural changes, and the conductive agent, with its large specific surface area and good dispersibility, can limit the excessive movement and agglomeration of the active material particles, maintain the integrity of the electrode structure, and thus reduce the thickness expansion rate of the battery cell.

[0099] When the positive electrode sheet includes 0.5% to 3% of a conductive agent and / or 0.5% to 5% of a binder, the electrode porosity can be increased, which is beneficial to the penetration of the electrolyte and the diffusion of lithium ions. It works synergistically with the conductive network to increase the migration rate of lithium ions, thereby increasing the discharge rate of the electrochemical device. At the same time, the conductive agent and the binder can improve the interfacial properties between the electrode and the electrolyte. The binder prevents excessive contact between the electrolyte and the active material, inhibits the occurrence of side reactions, and the conductive agent promotes charge transfer on the electrode surface, making the reaction more uniform and reducing local overheating and gas production. The two work together to reduce the internal pressure of the electrochemical device, thereby inhibiting the expansion of the battery cell thickness.

[0100] When the mass ratio of conductive carbon black and carbon nanotubes in the conductive agent is 0.6-2, the synergistic effect of the two helps to optimize the pore structure and surface properties inside the electrode. The porous structure of conductive carbon black can absorb more electrolyte, providing abundant transmission channels and storage sites for lithium ions. The presence of carbon nanotubes can further guide the transmission direction of lithium ions, making them diffuse more quickly and evenly in the electrode material. Therefore, during the charge and discharge process, lithium ions can be more efficiently embedded and extracted between the active material and the electrolyte, thereby improving the discharge rate of the electrochemical device. In addition, under high temperature conditions, the synergistic effect of conductive carbon black and carbon nanotubes can enhance the stability of the electrode structure. Conductive carbon black can be filled between the active material particles to play a buffering and supporting role, reducing the mutual extrusion and deformation of the active material particles due to thermal expansion. Carbon nanotubes can be interspersed in the entire electrode structure like a "skeleton", improving the overall mechanical strength of the electrode and limiting the displacement and agglomeration of the active material particles. The synergistic effect of the two can form a stable three-dimensional structure, effectively inhibiting the expansion and deformation of the electrode at high temperature, thereby reducing the thickness expansion rate of the battery cell.

[0101] It should be noted that the content of the conductive agent in the positive electrode sheet, the specific surface area of ​​the conductive agent, the content of the binder, and the mass ratio of the conductive carbon black and the carbon nanotubes in the conductive agent can all be detected using methods and instruments known in the art. For example, the positive electrode sheet can be obtained by disassembling the electrochemical device. For example, the binder is extracted from the sheet by a solvent extraction method using the fact that the binder is soluble in certain specific solvents, while the conductive agent and active substances are insoluble. The content of the binder is then determined by weighing or other methods, and the content of the conductive agent is then calculated. Using thermogravimetric analysis, according to the difference in thermal stability of conductive carbon black and carbon nanotubes at high temperatures, carbon nanotubes generally have relatively high thermal stability, and their weight loss within a certain temperature range is smaller than that of conductive carbon black. By analyzing the weight loss at different temperature stages in the thermogravimetric curve, the two can be distinguished, and the mass ratio of the two can be calculated based on the weight loss ratio.

[0102] Electrochemical Devices The present application provides an electrochemical device, which includes the above-mentioned positive electrode sheet, negative electrode sheet, separator and electrolyte. The electrochemical device has low internal resistance and high temperature storage cell thickness expansion rate, and also has high high temperature cycle capacity retention rate and charge and discharge performance.

[0103] In some specific embodiments, the electrochemical device satisfies at least one of the following conditions: (1) based on the total mass of the electrolyte, the electrolyte includes Z% of the dinitrile additive, and the specific surface area of ​​the conductive agent is Em 2 / g, the electrochemical device satisfies: 50≤E / Z≤1000, for example, E / Z can be 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, or a range consisting of any of the above values; (2) based on the total mass of the electrolyte, the electrolyte includes 0.5% to 5% of 2,2-difluoroethyl acetate, for example, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, or a range consisting of any of the above values; (3) the Dv50 of the positive electrode active material particles is Gμm, based on the total mass of the electrolyte, the electrolyte includes X % propyl propionate, the electrochemical device satisfies: 2≤G / X≤5, for example, G / X can be 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, or any range thereof; (5) the Dv50 of the positive electrode active material particles is 5μm~25μm, for example, it can be 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, or any range thereof; (4) based on the total mass of the electrolyte, the electrolyte includes 5%~30% propyl propionate, for example, it can be 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, or any range thereof.

[0104] In the above specific embodiments, when the electrochemical device satisfies: 14.2≤E / Z≤7500, the dinitrile additive can form a stable solid electrolyte interface (SEI) film on the electrode surface, which can prevent further reaction between the electrolyte and the electrode material, reduce corrosion and dissolution of the electrode material, and thus improve the cycle stability of the electrochemical device. The high specific surface area of ​​conductive carbon black helps to evenly distribute the active substances on the electrode surface, reduce the agglomeration and shedding of the active substances, and is also conducive to the uniform formation of the SEI film, ensuring the synergistic effect of the additive and conductive carbon black in improving the cycle stability, so that the electrochemical device can still maintain good performance after multiple charge and discharge cycles. In addition, the synergistic effect of the two makes the charge transfer inside the electrochemical device more efficient and the charge and discharge process smoother.

[0105] When the electrolyte includes 0.02% to 12.5% ​​of 2,2-difluoroethyl acetate in the total mass of the electrolyte, it helps to maintain the fluidity of the electrolyte under low temperature conditions, so that ions can be more smoothly transmitted inside the electrochemical device, thereby improving the charge and discharge efficiency and capacity of the electrochemical device at low temperatures, and reducing the performance degradation of the electrochemical device at low temperatures. At the same time, the additive can form a stable solid electrolyte interface (SEI) film on the electrode surface. This film can prevent the side reaction between the electrolyte and the electrode material, reduce the corrosion and dissolution of the electrode material, and inhibit the loss of active substances, thereby improving the cycle life of the electrochemical device, so that the electrochemical device can still maintain good performance after multiple charge and discharge cycles. However, too much 2,2-difluoroethyl acetate causes the electrolyte conductivity to decrease, making the CEI film loose, thereby reducing the cycle performance and rate performance of the electrochemical device. Further preferably, based on the total mass of the electrolyte, the mass percentage of 2,2-difluoroethyl acetate is 0.5%-5%, which can better improve the cycle performance and rate performance of the electrochemical device.

[0106] When the electrochemical device satisfies: 0.125≤G / X≤0.83, it helps to achieve a good match between the positive electrode active material particles and the propyl propionate in the electrolyte. Propyl propionate can better infiltrate the surface of the active material particles, increase the contact area between the electrode and the electrolyte, facilitate the transmission of ions at the interface, reduce the interface resistance, and thus improve the charge and discharge efficiency of the electrochemical device. G / X that is too small will dilute the Li in the electrolyte. + The content will reduce the conductivity of the electrochemical device, and the formed CEI film will be loose and too thick, thereby reducing the cycle performance and rate performance of the electrochemical device.

[0107] It should be noted that the components in the electrolyte can be detected using methods and instruments known in the art. For example, the electrolyte can be obtained by disassembling the electrochemical device, and ion chromatography (IC) can be used for testing. The retention time can be used to qualitatively identify some components in the electrolyte (such as lithium salts), and the corresponding types and mass percentages can be calculated by peak area; gas chromatography-mass spectrometry (GC-MS) can be used to detect the types and mass percentages of some components in the electrolyte (such as organic solvents).

[0108] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.

[0109] In some embodiments, the electrolyte may include additives such as diethylene sulfate (DTD), vinylene sulfate (VC), 1,3-propane sultone and may further include fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate or bis(trifluoroethyl) carbonate.

[0110] In some embodiments, in addition to LiFSI and LiPO2F2, the electrolyte may further include an ionizable lithium salt, and the ionizable lithium salt includes at least one of LiPF6, LiSbF6, LiAsF6, LiClO4, LiN(C2F5SO2)2, CF3SO3Li, LiC(CF3SO2)3 or LiC4BO8. The concentration of the ionizable lithium salt in the electrolyte is not particularly limited, preferably 0.5 mol / L or more, more preferably 0.8 mol / L or more, and further preferably 1.0 mol / L or more. In addition, it is preferably 3 mol / L or less, more preferably 2 mol / L or less, and further preferably 1.7 mol / L or less. If the concentration of these ionizable lithium salts is too low, it may cause the number of mobile lithium ions in the electrolyte to be insufficient. On the other hand, if the concentration of these ionizable lithium salts is too high, it may cause the viscosity of the electrolyte to increase, resulting in an increase in the impedance of the electrolyte, which reduces the migration rate of lithium ions, and thus may cause the performance of the electrochemical device to decrease.

[0111] In some embodiments, the electrolyte may further include at least one of fluoroether, fluoroethylene carbonate or ether solvents. In some embodiments, the electrolyte may further include a non-aqueous solvent. The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof.

[0112] The carbonate compound may include, in addition to the chain carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0113] In addition to diethyl carbonate (DEC) defined in the present application, examples of chain carbonate compounds may include ethyl propionate (EP), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of the fluorinated carbonate compound are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or a combination thereof.

[0114] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.

[0115] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0116] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.

[0117] The present application also provides an electrochemical device, comprising the above-mentioned electrolyte. In some embodiments, the electrochemical device further comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet and the negative electrode sheet are separated by a separator disposed therebetween. In some embodiments, the positive electrode sheet comprises a positive current collector and a positive electrode active material layer disposed on the positive current collector, the positive electrode active material layer may include a positive electrode active material and an additive, and the negative electrode sheet comprises a negative current collector and a negative electrode active material layer disposed on the negative current collector, the negative electrode active material layer may include a negative electrode active material.

[0118] In some embodiments, the negative electrode plate may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may be disposed on one or both sides of the negative electrode current collector. In some embodiments, the negative electrode current collector may be at least one of a copper foil, a nickel foil, or a carbon-based current collector. In some embodiments, the thickness of the negative electrode current collector may be 1 μm to 200 μm. In some embodiments, the negative electrode active material layer may be coated only on a partial area of ​​the negative electrode current collector. In some embodiments, the thickness of the negative electrode active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only and other suitable thicknesses may be used.

[0119] In some embodiments, as described above, the negative electrode active material layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes at least one of natural graphite, artificial graphite, or a silicon-based material. In some embodiments, the silicon-based material includes at least one of silicon, a silicon-oxygen compound, a silicon-carbon compound, or a silicon alloy.

[0120] In some embodiments, the negative electrode active material layer may also include a negative electrode conductor and / or a negative electrode binder. The negative electrode conductor may include at least one of carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the negative electrode binder may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylic acid salt, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, or styrene-butadiene rubber. It should be understood that the materials disclosed above are only exemplary, and the negative electrode active material layer may be any other suitable material. In some embodiments, the mass ratio of the negative electrode active material, the negative electrode conductor, and the negative electrode binder in the negative electrode active material layer may be (80~99): (0.5~10): (0.5~10), and it should be understood that this is only exemplary and not intended to limit the present application.

[0121] In some embodiments, the positive electrode plate includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer may be located on one side or both sides of the positive current collector. In some embodiments, the positive current collector may be made of aluminum foil, and of course, other positive current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive current collector may be 1 μm to 200 μm. In some embodiments, the positive active material layer may be coated only on a partial area of ​​the positive current collector. In some embodiments, the thickness of the positive active material layer may be 20 μm to 490 μm, and further preferably, the thickness may be 20 μm to 400 μm, and further, it may be 40 μm to 120 μm, and further, it may be 40 μm to 90 μm.

[0122] In some embodiments, as described above, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the above positive electrode active material may be doped and / or coated. Further preferably, the positive electrode active material is lithium cobalt oxide or lithium iron phosphate.

[0123] In some embodiments, the surface of the positive electrode material includes lithium phosphate and / or lithium niobate, the mass ratio of the two is 1:3 to 1:1, and the thickness of the covering layer is 1 μm to 1.8 μm.

[0124] In some embodiments, the surface of the positive electrode material includes lithium dihydrogen phosphate or aluminum dihydrogen phosphate, and the mass percentage of lithium dihydrogen phosphate or aluminum dihydrogen phosphate is M% based on the total mass of the positive electrode active material layer, and 5≤M≤20.

[0125] In some embodiments, the substrate of the isolation film includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the safety of the battery through the shutdown effect. In some embodiments, the thickness of the isolation film as a whole is in the range of about 3 μm to 480 μm.

[0126] In some embodiments, the surface of the isolation membrane may further include a porous layer, which is disposed on at least one surface of the isolation membrane, and the porous layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece. One surface of the separator can also include a high melting point crystalline polymer or a high temperature resistant amorphous polymer, and the high temperature resistant resin includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene, polyvinylidene fluoride and cycloolefin copolymers. The high melting point crystalline polymer includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene or polyvinylidene fluoride, and the high temperature resistant amorphous polymer includes cycloolefin copolymers. Based on the mass of the polyolefin porous substrate, the mass percentage z of the high temperature resistant resin is 2.5% to 9%. For example, the mass percentage z of the high temperature resistant resin is 2.5%, 3%, 5%, 7%, 8%, 9% or a range composed of any two of the values. When the above-mentioned types of high temperature resistant resins are added to the polyolefin porous substrate and the mass percentage of the high temperature resistant resin is regulated within the above range, it is beneficial to increase the melting temperature of the separator, improve the strength and high temperature performance of the electrochemical device.

[0127] In some embodiments, the electrochemical device is a lithium-ion battery, but the present application is not limited thereto.

[0128] In some embodiments of the present application, taking lithium-ion batteries as an example, the positive electrode sheet, the isolation membrane, and the negative electrode sheet are wound or stacked in sequence to form an electrode assembly, and then placed in a shell such as an aluminum-plastic film for packaging, and the electrolyte is injected, formed, and packaged to make a lithium-ion battery.

[0129] Preparation method of conductive carbon black The raw natural gas is placed in a reactor to undergo a cracking reaction at a high temperature of 1000°C to 1500°C to generate carbon black particles, which are blown out of the furnace tube, cooled to room temperature, and collected. The present application does not particularly limit the type of the above raw materials, as long as the purpose of the present application can be achieved. For example, the raw materials may include but are not limited to acetylene or tar.

[0130] Electronic Devices Embodiments of the present application also provide electronic devices including the above-mentioned electrochemical devices. The electronic devices of the embodiments of the present application are not particularly limited, and they can be any electronic devices known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0131] Test Section The test method is as follows: 1. Under the conditions of ambient temperature of 25℃ and battery state of charge of 20%, measure the DC internal resistance of the battery for 1 second (1s DCR@25℃ 20% SOC): Take the lithium ion battery in the embodiment or comparative example and perform the following tests at 25±2°C: (1) stand for 2h; (2) then charge at a constant current of 1.0C to 4.50V, and charge at a constant voltage at 4.50V until the current is less than or equal to 0.025C; stand for 2h; (3) then discharge at a constant current of 0.2C to 3.0V, taking the discharge capacity of this step as variable C1, and stand for 5h; (4) then charge at a constant current of 1.0C1 to 4.3V, and charge at a constant voltage at 4.3V until the current is less than or equal to 0.025C1; stand for 10min; (5) then discharge at a constant current of 0.1C1 to a capacity of 0.2C1, stand for 15min, record its voltage as V0, and then discharge at a cross current of 1.0C1 for 1s, record the voltage at this time as V1, then the 1s DCR at 25°C 20%SOC is (V0-V1) / 1.0C1.

[0132] 2. 85℃, 8h storage cell thickness expansion rate: In an environment of 25±3℃, charge the cell at a constant current of 0.5C to 4.50V, and then charge at a constant voltage of 4.50V to 0.025C. The initial thickness of the cell is recorded as H1. Put the cell in a high-temperature furnace at 85±3℃ for 8h, and then test the cell thickness in situ as T2. The cell storage thickness expansion rate is recorded as (T2-T1) / T1.

[0133] 3. Cycle capacity retention rate: Take the lithium ion battery in the embodiment or comparative example and perform the following test at 45±2°C: (1) Let stand for 2 hours, discharge at 0.5C constant current to 3.0V, and let stand for 5 minutes; (2) Charge at 1.0C constant current to 4.5V, and charge at 4.5V with constant voltage until the current is less than or equal to 0.05C; let it stand for 5 minutes; then discharge at 0.5C constant current to 3.0V, and record the discharge capacity at this time as C1; let it stand for 5 minutes; repeat the above steps for 49 cycles; then perform the 50th cycle, charge at 1.0C constant current to 4.5V, and charge at 4.5V with constant voltage until the current is less than or equal to 0.05C; let it stand for 5 minutes; then discharge at 0.2C constant current to 3.0V; (3) Then, after the above step (2) is cycled 10 times, the battery is charged to 4.5 V at a constant current of 1.0 C, and then charged to a current of less than or equal to 0.05 C at a constant voltage of 4.5 V; left to stand for 5 min; then, discharged to 3.0 V at a constant current of 0.5 C, and the capacity of the lithium-ion battery at the 501st cycle is recorded as C501; the capacity retention rate of the lithium-ion battery after 500 cycles at 45°C is C501 / C1.

[0134] 4.Charging rate: Take the lithium ion battery in the embodiment or comparative example and perform the following test at 25±2°C: (1) Let stand for 2 hours, discharge at 0.5C constant current to 3.0V, and let stand for 5 minutes; (2) Charge at 1.0C constant current to 4.50V, and charge at 4.5V constant voltage until the current is less than or equal to 0.05C; let it stand for 5 minutes; then discharge at 0.2C constant current to 3.0V, and record the discharge capacity at this time as C0; Then discharge at 3.5C0 constant current to 4.40V, then discharge at 2.6C0 constant current to 4.35V; then discharge at 2.2C0 constant current to 4.48V; then discharge at 1.8C0 constant current to 4.50V, and then charge at 4.50V constant voltage to 0.05C0; record the total charging capacity C1 in this process, the charging capacity of "3.5C0 constant current discharge to 4.40V" is C2, and the 3.5C discharge rate is C2 / C1.

[0135] 5. Volatile matter test of conductive carbon black: First, dry the crucible and the crucible cover at 950℃ for half an hour, then weigh them after cooling to room temperature. Dry the conductive carbon black with a mass of m at 125℃ for 10 minutes, pour the dried carbon black into the dried crucible and cover the crucible with the crucible cover. The total weight is M1. Put them together in a muffle furnace at 950℃, keep warm for 7 minutes, and then air cool them to room temperature. The total weight is M2, and the volatile matter ratio is: (M1-M2) / m, where m is 2g.

[0136] 6. Specific surface area test of conductive carbon black: The multi-point adsorption BET method is used to place the dehydrated and degassed sample into the sample tube of the instrument. At liquid nitrogen temperature (77K), nitrogen at different pressures is introduced into the sample tube to measure the amount of nitrogen adsorbed on the sample surface. Then, according to the BET equation, the inverse of the adsorption amount is plotted against the relative pressure to obtain a straight line. The specific surface area of ​​the sample can be calculated from the slope and intercept of the straight line.

[0137] 7. Element test in conductive carbon black: Take 0.5g of carbon powder and dissolve it with 10ml of nitric acid, then put it into ICP-OES, Avio 200 element tester for testing. During the test, the pump speed of the equipment was adjusted to 1.5mL / min, the RF power was 1300W, the observation angle was vertical, and the observation height was 15ml. After the test, the results can be directly output from the instrument.

[0138] 8. Magnetic impurities test in conductive carbon black: Dissolve m0 (200g) conductive carbon in 300ml deionized water and put it into a two-dimensional horizontal rolling mixer. Use a 52mm long, 17mm diameter magnetic bar with a magnetic field strength of 6000±500GS to adsorb magnetic impurities. The mixer rotates at 60r / min for 30min. Then take out the magnetic bar to wash off the magnetic impurities and digest them with 10ml (1+1) aqua regia. Then ICP test the types of magnetic impurities and the total mass of Fe, Cr, Ni, and Zn is m1, then the magnetic impurity content is m1 / m0.

[0139] 9. Ash content test in conductive carbon black: Take carbon powder weighing m0 (m0=2.0g) and burn it at 800℃ for 5h. Then weigh the remaining ash with a weight of m1. The ash content is m1 / m0.

[0140] 10. Volatile loss temperature test of conductive carbon black: Take 2g of carbon black and bake it at 60℃ for 30min. Then take 0.1~0.2g of it for TG test. Raise the temperature to 900℃ at a rate of 10℃ / min to obtain the temperature-weight curve. Find the temperature point where the weight starts to lose, which is the volatile matter loss temperature.

[0141] 11. Average particle size test of carbon black unit: (1) disassembling a lithium-ion battery to obtain a positive electrode sheet; (2) soaking the positive electrode sheet in DMC at room temperature for 30 minutes, taking it out, and then drying it; (3) taking the positive electrode sheet obtained in step (2), corroding it with concentrated sulfuric acid, filtering it to obtain a conductive agent, and after drying, testing the primary particle size of the carbon black particles under TEM at a magnification of 80,000 times, testing 50 particles, and taking the average of all test values ​​as the final result.

[0142] Example The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0143] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.

[0144] Example 1-1 The raw materials are placed in a reaction furnace to undergo a cracking reaction at a high temperature of 1000°C to 1500°C to generate carbon black particles, which are blown out of the furnace tube, cooled and collected. The parameters of conductive carbon black are shown in Table 1.

[0145] Positive electrode: lithium cobalt oxide, conductive agent and polyvinylidene fluoride are mixed in a weight ratio of 97.7:1:1.3 and added into N-methylpyrrolidone, and stirred into a uniform slurry. The slurry is stirred, coated, dried, rolled and spot welded to the pole ear to obtain the positive electrode of the battery, wherein the mass ratio of conductive carbon black to carbon nanotubes in the conductive agent is 1.

[0146] Electrolyte: In a glove box filled with argon, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate were mixed in a mass ratio of 3:4:3, 2% of the total mass of the electrolyte was added with 2,2-difluoroethyl acetate, 1% of the total mass of the electrolyte was added with a dinitrile additive and 20% of the total mass of the electrolyte was added with propyl propionate, and a certain amount of lithium hexafluorophosphate was added so that the final mass percentage of lithium hexafluorophosphate in the total electrolyte was 9%.

[0147] Isolation membrane: The isolation membrane uses a 5μm thick polyethylene substrate (PE), and a 2μm alumina ceramic layer is coated on both sides of the isolation membrane. Finally, 2.5mg / cm 2 Polyvinylidene fluoride (PVDF), dried.

[0148] Negative electrode sheet: Mix the negative electrode active material artificial graphite, conductive agent conductive carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) at a weight ratio of 97:1:1:1, add deionized water, and stir evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 80%. The negative electrode slurry is evenly coated on one side of the negative electrode collector copper foil, and dried at 110°C to obtain a negative electrode sheet coated with a negative electrode active material layer with a thickness of 90μm on one side. Repeat the above steps on the other side of the negative electrode collector copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 476mm×93.5mm is obtained. The surface resistance test of the negative electrode sheet is 0.002mΩ / cm 2 .

[0149] Preparation of lithium-ion batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain an electrode assembly. After welding the pole ears, place the electrode assembly in an outer packaging aluminum-plastic film, remove moisture at 80°C, inject the above-mentioned electrolyte, and obtain a lithium-ion battery through vacuum packaging, standing, formation, shaping, capacity testing and other processes.

[0150] Examples 1-2 to 1-16, Comparative Examples 1-1 to 1-2 The preparation of the lithium-ion battery is substantially the same as that of Example 1-1, except for the M / N, volatile matter content M, specific surface area N, oxygen content A, hydrogen content B, A / B of the conductive carbon black, and the infrared absorption spectrum of the conductive carbon black at 1700-1730 cm -1 The peak at 2500~300cm -1 The specific parameters are shown in Table 1.

[0151] The lithium-ion battery was subjected to 1s DCR@25℃ 20% SOC test and 85℃, 8h storage cell thickness expansion rate test. The results are shown in Table 1.

[0152] Table 1

[0153] According to Table 1, compared with the comparative example, the M / N of each embodiment is controlled within the range of the present application, and the 1sDCR@25℃ 20% SOC and the 85℃, 8h storage cell thickness expansion rate of the lithium-ion battery are significantly improved. When the conductive carbon black of the present application is used, and the 85℃, 8h storage cell thickness expansion rate of the conductive carbon black meets the range of the present application, the two work together, and the lithium-ion battery has good stability and low DC internal resistance.

[0154] According to Examples 1-1 to 1-7 and Comparative Examples 1-1 to 1-2, when the conductive carbon black satisfies one of: 0.003≤M / N≤0.02, 0.1≤M≤0.7, and 30≤N≤80, the lithium-ion battery has better stability and lower DC internal resistance.

[0155] On this basis, according to Examples 1-3 to 1-5, when the conductive carbon black satisfies: 0.005≤M / N≤0.01, and / or, 0.3≤M≤0.6, the lithium-ion battery has better high temperature stability and lower DC internal resistance.

[0156] According to Examples 1-8 to 1-14, the conductive carbon black satisfies the following conditions: 0.5≤A / B≤2, 0.05≤A≤0.3, and the infrared absorption spectrum of the conductive carbon black is 1700-1730cm -1 The peak at 2500~300cm -1 When the ratio of the peak values ​​at is between 0.2 and 0.7, the lithium-ion battery has better stability and lower DC internal resistance.

[0157] On this basis, according to Examples 1-8 to 1-14, the conductive carbon black satisfies: 0.8≤A / B≤1.5, 0.08≤A≤0.15 and the infrared absorption spectrum of the conductive carbon black is 1700~1730cm -1 The peak at 2500~300cm -1 When the ratio of the peak values ​​at is between 0.3 and 0.6, the lithium-ion battery has better stability and lower DC internal resistance.

[0158] Example 2-1 to Example 2-14 The preparation of the lithium-ion battery is substantially the same as that of Example 1-1, with the only difference being the magnetic impurity content, ash content, volatile matter loss start temperature, and half-width of the (002) crystal plane diffraction peak in the X-ray diffraction spectrum of the conductive carbon black. The specific parameters are shown in Table 2.

[0159] The lithium-ion battery was subjected to a 45°C, 500-cycle capacity retention test. The results are shown in Table 2.

[0160] Table 2

[0161] According to Table 2, the magnetic impurity content, ash content, volatile matter loss start temperature and half-width of the (002) crystal plane diffraction peak in the X-ray diffraction spectrum of the conductive carbon black are controlled within the scope of the present application, and the lithium-ion battery has good high-temperature cycle performance and charge and discharge performance.

[0162] According to Example 1-1, Example 2-1 to Example 2-3 and Example 2-10, when the magnetic impurity content of the conductive carbon black is 50 ppb to 500 ppb of magnetic impurities and / or the ash content is 50 ppb to 500 ppb, the lithium-ion battery has better high temperature cycle performance.

[0163] According to Example 1-1, Example 2-4 to Example 2-6, Example 2-11, and Example 2-12, when the volatile matter loss temperature of the conductive carbon black is 550°C to 950°C, the lithium-ion battery has good high-temperature cycle performance.

[0164] According to Example 1-1, Example 2-7 to Example 2-9 and Example 2-13 and Example 2-14, when the half-width at half-height of the (002) crystal plane diffraction peak in the X-ray diffraction pattern of the conductive carbon black is 1°~5°, the lithium-ion battery has good high-temperature cycle performance.

[0165] According to Example 1-1 and Example 2-8, when the half-width at half maximum of the (002) crystal plane diffraction peak in the X-ray diffraction spectrum of the conductive carbon black is 1.5°~3°, the lithium-ion battery has better high-temperature cycle performance.

[0166] Example 3-1 to Example 3-29 The preparation of the lithium-ion battery is substantially the same as that of Example 1-1, with the only differences being W2 / (E×W1), E, ​​W1, W2, C, D and C / D. The specific parameters are shown in Table 3.

[0167] The lithium-ion battery was subjected to a 3.5C discharge rate test and an 85°C, 8h storage cell thickness expansion rate test. The results are shown in Table 3.

[0168] Table 3

[0169] Continue Table 3

[0170] According to Table 3, W2 / (E×W1), E, ​​W1, W2, C, D and C / D are controlled within the scope of the present application, and the lithium-ion battery has good high temperature stability and charge and discharge performance.

[0171] According to Example 1-1, Example 3-1 to Example 3-8 and Example 3-22, Example 3-23, when the positive electrode plate satisfies: 0.004×E×W1≤W2≤0.014×E×W1 and / or 40≤E≤300, the lithium-ion battery has good high temperature stability and charge and discharge performance.

[0172] On this basis, according to Example 1-1, Example 3-3 to Example 3-6, when the positive electrode plate satisfies: 0.007×E×W1≤W2≤0.012×E×W1 and / or 100≤E≤200, the lithium-ion battery has better high temperature stability and charge and discharge performance.

[0173] According to Examples 1-1, 3-9 to 3-14, 3-24 and 3-25, when the mass ratio of conductive carbon black to carbon nanotubes in the conductive agent is 0.6 to 2, the lithium-ion battery has good high temperature stability and charge and discharge performance.

[0174] On this basis, according to Example 1-1, Example 3-11 to Example 3-12, when the mass ratio of conductive carbon black to carbon nanotubes in the conductive agent is 0.8-1.5, the lithium-ion battery has better high temperature stability and charge and discharge performance.

[0175] According to Example 1-1, Example 3-15 to Example 3-21 and Example 3-26 to Example 3-29, when the conductive carbon black satisfies at least one of: 25≤C / D≤150, 1000≤C≤6000 and 30≤D≤70, the lithium-ion battery has good high temperature stability and charge and discharge performance.

[0176] On this basis, according to Example 1-1, Example 3-16 to Example 3-19, when the conductive carbon black satisfies at least one of: 25≤C / D≤150, 1500≤C≤5000 and 40≤D≤60, the lithium-ion battery has better high temperature stability and charge and discharge performance.

[0177] Example 4-1 to Example 4-20 The preparation of the lithium-ion battery is substantially the same as that of Example 1-1, with the only differences being E / Z, the content of 2,2-difluoroethyl acetate in the electrolyte, G, X and G / X. The specific parameters are shown in Table 4.

[0178] The lithium-ion battery was subjected to a 45°C, 500-cycle capacity retention test and a 3.5C discharge rate test. The results are shown in Table 4.

[0179] Table 4

[0180] According to Table 4, E / Z, G and G / X are controlled within the range of the present application, and the lithium-ion battery has good high-temperature cycle performance and charge-discharge performance.

[0181] According to Example 1-1, Example 4-1 to Example 4-5, Example 4-16, and Example 4-17, when the electrochemical device satisfies: 50≤E / Z≤1000, the lithium-ion battery has good high-temperature cycle performance and charge-discharge performance.

[0182] According to Example 1-1, Example 4-6 to Example 4-9, and Example 4-20, when the electrolyte includes 0.5% to 5% of 2,2-difluoroethyl acetate, the lithium-ion battery has better high-temperature cycle performance and charge and discharge performance.

[0183] According to Example 1-1, Example 4-10 to Example 4-15, Example 4-18 and Example 4-19, when the electrochemical device satisfies any one of: 5≤G≤25, 5≤X≤30 and 2≤G / X≤5, the lithium-ion battery has good high temperature cycle performance and charge and discharge performance.

[0184] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no structural conflict. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A conductive carbon black, characterized in that: The conductive carbon black comprises a plurality of carbon black units and pores between adjacent carbon black units; Based on the total mass of the conductive carbon black, the mass percentage of volatile matter in the conductive carbon black is M%, and the specific surface area of ​​the conductive carbon black is Nm 2 / g, the conductive carbon black satisfies: 0.003≤M / N≤0.

02.

2. The conductive carbon black according to claim 1, characterized in that The conductive carbon black satisfies: 0.005≤M / N≤0.

01.

3. The conductive carbon black according to claim 1, characterized in that Based on the total mass of the conductive carbon black, the mass percentage of volatile matter in the conductive carbon black is 0.1% to 0.7%, and / or the specific surface area of ​​the conductive carbon black is 30m 2 / g~80m 2 / g.

4. The conductive carbon black according to claim 3, characterized in that Based on the total mass of the conductive carbon black, the mass percentage of volatile matter in the conductive carbon black is 0.3% to 0.6%, and / or the specific surface area of ​​the conductive carbon black is 50m 2 / g~60m 2 / g.

5. The conductive carbon black according to claim 1, characterized in that Based on the total mass of the conductive carbon black, the conductive carbon black includes A% of oxygen elements, the conductive carbon black includes B% of hydrogen elements, and the conductive carbon black satisfies: 0.5≤A / B≤2.

6. The conductive carbon black according to claim 5, characterized in that The conductive carbon black satisfies: 0.8≤A / B≤1.

5.

7. The conductive carbon black according to claim 1, characterized in that Based on the total mass of the conductive carbon black, the conductive carbon black includes 0.05% to 0.3% of oxygen element, and / or the conductive carbon black includes 0.05% to 0.3% of hydrogen element.

8. The conductive carbon black according to claim 7, characterized in that Based on the total mass of the conductive carbon black, the conductive carbon black includes 0.08% to 0.15% of oxygen element, and / or the conductive carbon black includes 0.08% to 0.15% of hydrogen element.

9. The conductive carbon black according to any one of claims 1 to 8, characterized in that The conductive carbon black satisfies at least one of the following: (1) Based on the total mass of the conductive carbon black, the conductive carbon black includes 100 ppb to 500 ppb of magnetic impurities; (2) The conductive carbon black comprises 50 ppb to 500 ppb of ash based on the total mass of the conductive carbon black; (3) The volatile matter loss temperature of the conductive carbon black is 550°C to 950°C; (4) The Dv50 of the conductive carbon black is 1000nm~6000nm; (5) The average particle size of the carbon black unit is 30nm~70nm; (6) The powder resistivity of the conductive carbon black is 25 mΩ·cm to 45 mΩ·cm; (7) The half-width at half maximum of the (002) crystal plane diffraction peak in the X-ray diffraction pattern of the conductive carbon black is 1° to 5°; (8) The infrared absorption spectrum of the conductive carbon black is 1700-1730 cm -1 The peak at 2500~300cm -1 The ratio of the peak value at is 0.2~0.7; (9) The conductive carbon black comprises a plurality of carbon black units stacked to form a core and a plurality of branches connected to the core; (10) The Dv50 of the conductive carbon black is Cnm, the average particle size of the carbon black unit is Dnm, and the conductive carbon black satisfies: 25≤C / D≤150.

10. The conductive carbon black according to claim 9, characterized in that The conductive carbon black satisfies at least one of the following: (1) The Dv50 of the conductive carbon black is 1500nm~5000nm; (2) The average particle size of the carbon black unit is 40nm~60nm; (3) The powder resistivity of the conductive carbon black is 30 mΩ·cm to 40 mΩ·cm; (4) The half-width at half maximum of the (002) crystal plane diffraction peak in the X-ray diffraction pattern of the conductive carbon black is 1.5° to 3°; (5) In the infrared absorption spectrum of the conductive carbon black, the wavelengths of 1700-1730 cm -1 The peak at 2500~300cm -1 The ratio of the peak values ​​at is 0.3~0.

6.

11. A positive electrode sheet, characterized in that: The invention comprises a binder, positive electrode active material particles and a conductive agent, wherein the conductive agent comprises the conductive carbon black and carbon nanotubes according to any one of claims 1 to 10.

12. The positive electrode sheet according to claim 11, characterized in that: The positive electrode plate satisfies at least one of the following: (1) The specific surface area of ​​the conductive agent is Em 2 / g, based on the total mass of the positive electrode sheet, the positive electrode sheet includes W1% of a conductive agent and W2% of a binder, and the positive electrode sheet satisfies: 0.004×E×W1≤W2≤0.014×E×W1; (2) The specific surface area of ​​the conductive agent is 40 m 2 / g~300m 2 / g; (3) Based on the total mass of the positive electrode sheet, the positive electrode sheet includes 0.5% to 3% of a conductive agent; (4) Based on the total mass of the positive electrode sheet, the positive electrode sheet includes 0.5% to 5% of a binder; (5) The mass ratio of the conductive carbon black to the carbon nanotubes in the conductive agent is 0.6-2.

13. The positive electrode sheet according to claim 12, characterized in that: The positive electrode plate satisfies at least one of the following: (1) The positive electrode sheet satisfies: 0.007×E×W1≤W2≤0.012×E×W1; (2) The specific surface area of ​​the conductive agent is 100 m 2 / g~200m 2 / g; (3) Based on the total mass of the positive electrode sheet, the positive electrode sheet includes 0.8% to 2.5% of a conductive agent; (4) Based on the total mass of the positive electrode sheet, the positive electrode sheet includes 1.0% to 3.0% of a binder; (5) The mass ratio of the conductive carbon black to the carbon nanotubes in the conductive agent is 0.8-1.

5.

14. An electrochemical device, characterized in that: It comprises the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte as described in any one of claims 11 to 13.

15. The electrochemical device according to claim 14, characterized in that The electrochemical device satisfies at least one of the following: (1) Based on the total mass of the electrolyte, the electrolyte includes Z% of a dinitrile additive, and the specific surface area of ​​the conductive agent is Em 2 / g, the electrochemical device satisfies: 50≤E / Z≤1000; (2) Based on the total mass of the electrolyte, the electrolyte includes 0.5% to 5% of 2,2-difluoroethyl acetate; (3) The Dv50 of the positive electrode active material particles is G μm, the electrolyte includes X% of propyl propionate based on the total mass of the electrolyte, and the electrochemical device satisfies: 2≤G / X≤5; (5) The Dv50 of the positive electrode active material particles is 5 μm to 25 μm; (4) Based on the total mass of the electrolyte, the electrolyte includes 5% to 30% of propyl propionate.

16. An electronic device, characterized in that: An electrochemical device comprising any one of claims 14 to 15.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    CN106257717A

  • Preparation method and application of superconducting carbon black

    CN117004253A

  • Positive plate and application thereof

    CN118335901A

  • Positive plate and battery

    CN119650578A

  • Electrically conductive carbon black

    JP1989272667A